A platform for computer-assisted multilingual literacy development - Mudimba, Bwini Chizabubi (Rhodes University, Faculty of Science, Department of Computer Science, 2011)
FundaWethu is reading software that is designed to deliver reading lessons to Grade R-3 (foundation phase) children who are learning to read in a multilingual context. Starting from a premise that the system should be both educative and entertaining, the system allows literacy researchers or teachers to construct rich multimedia reading lessons, with text, pictures (possibly animated), and audio files. Using the design-based research methodology which is problem driven and iterative, we followed a user-centred design process in creating FundaWethu. To promote sustainability of the software, we chose to bring teachers on board as "co-designers" using the lesson authoring tool. We made the authoring tool simple enough for use by non computer specialists, but expressive enough to enable a wide range of beginners reading exercises to be constructed in a number of different languages (indigenous South African languages in particular). This project therefore centred on the use of designbased research to build FundaWethu, the design and construction of FundaWethu and the usability study carried out to determine the adequacy of FundaWethu.
Keywords: FundaWethu; Language acquisition -- Computer-assisted instruction; Language arts (Elementary) -- Computer-assisted instruction; Language and education; Education, Bilingual; Computer-assisted instruction; Educational technology; Computers and literacy